EMI (English-medium instruction) in Indonesian higher education - Bolton, Kingsley (2023)
This article reports on the investigation of English-medium instruction (EMI) in Indonesian higher education. Two separate but related studies were carried out. In Phase One, a mixed method approach using a questionnaire and interviews was used at a private university in Jakarta in order to gauge the responses of undergraduates studying a range of subjects through English. The results of Phase One suggested that the students at this university generally had high levels of proficiency in English and coped rather well with EMI. Phase Two of the study involved interviewing 17 educators across multiple institutions, and the results of this provided a nuanced picture of the implementation of EMI in higher education across this diverse multilingual nation.